2000
DOI: 10.1034/j.1600-0773.2000.d01-35.x
|View full text |Cite
|
Sign up to set email alerts
|

Lesioning of Locus coeruleus Projections by DSP-4 Neurotoxin Treatment: Effect on Amphetamine-Induced Hyperlocomotion and Dopamine D2 Receptor Binding in Rats

Abstract: DSP-4 is a neurotoxin highly selective for the noradrenergic nerve terminals of the locus coeruleus projections. Data on the effect of DSP-4 treatment on amphetamine-induced hyperlocomotion are contradictory. In this study, DSP-4 (50 mg/kg) caused reduction of noradrenaline levels by 70% in the cerebral cortex and by 79% in the cerebellum. This treatment resulted in upregulation of dopamine D2 receptors in the striatum as evidenced by [3H]-raclopride binding. In an open field test, DSP-4 reduced locomotor acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…We propose that under ''basal'' conditions, DbhϪ/Ϫ mice have very little DA signaling, but on those rare occasions that a burst of DA is released in the striatum, the hypersensitive DA receptors cause a hyperdopaminergic response manifesting as a dyskinetic-like movement. In support of this hypothesis, DSP4 lesions produce both DAreceptor hypersensitivity (49) and dyskinesias (this study), and the D1/D2 antagonist flupenthixole partially attenuates dyskinesias in DbhϪ/Ϫ mice. NE replacement with DOPS in DbhϪ/Ϫ mice worsened dyskinesias, probably by acutely restoring normal DA release without normalizing DA-receptor sensitivity.…”
Section: Discussionsupporting
confidence: 56%
“…We propose that under ''basal'' conditions, DbhϪ/Ϫ mice have very little DA signaling, but on those rare occasions that a burst of DA is released in the striatum, the hypersensitive DA receptors cause a hyperdopaminergic response manifesting as a dyskinetic-like movement. In support of this hypothesis, DSP4 lesions produce both DAreceptor hypersensitivity (49) and dyskinesias (this study), and the D1/D2 antagonist flupenthixole partially attenuates dyskinesias in DbhϪ/Ϫ mice. NE replacement with DOPS in DbhϪ/Ϫ mice worsened dyskinesias, probably by acutely restoring normal DA release without normalizing DA-receptor sensitivity.…”
Section: Discussionsupporting
confidence: 56%
“…It has also been shown that extensive selective lesions of the locus coeruleus projections may reduce the psychostimulant effect of amphetamine in a novel environment (Harro et al, 2000). This strengthens the finding that exposure to a white background sound improves performance in children with ADHD Söderlund et al, 2010aSöderlund et al, , 2010b.…”
Section: Discussionmentioning
confidence: 73%
“…Third, LRA in DbhϪ͞Ϫ mice is not blocked by prazosin, which would prevent receptor activation by either NE or DA. Fourth, a few studies demonstrate similar changes in DA receptor and amphetamine sensitivity in animals with lesions of the locus coeruleus that do not result in ectopic DA (17,18). However, because ectopic DA remains a possible mechanism, it will be important to examine LRA in mice that lack NE without producing ectopic DA.…”
Section: Discussionmentioning
confidence: 99%